Ultracapacitor applications - Miller, John M., 1949- (Institution of Engineering and Technology, 2011)
This text takes a critical look at physical storage of electricity in the devices known collectively as electrochemical capacitors and particularly as ultracapacitors.
Keywords: Supercapacitors.; elektronické knihy; electronic books